Marketing Mix Affecting Accommodation Service Buying Decisions of Backpacker Tourist Traveling at Inner Rattanakosin Island in Bangkok, Thailand - Katanyu Hiransomboon (My University, 2012)
This research is to study the buying behavior and the level of marketing mix (consisting of service product, price, promotion, place/channel of contact, process, people, and physical evidence) on the accommodation service buying decision of backpacker tourists. A direct interview survey of 417 randomly selected backpackers who visited the inner Rattanakosin Island in Bangkok, Thailand is used. The statistical method used includes frequency, percentage, mean, standard deviation. The results indicated that most backpackers are men, age 20-30 years old, work as the employees in private companies, bachelor degree, annual income is more than 10,000 to 50,000 US$ and come from Europe. Accommodation service buying behavior includes daily rental expense is more than 10 to 20 US$, spend a week or less, prefer to stay in the reasonable price guesthouse located nearby tourist site, make decision by themselves, make a reservation and get the information from website. The important levels of marketing mix ranking respectively are 1)service personnel factor in having a good manner with the friendly personality, 2)physical evidence factor in having a clean place, 3)accommodation product and service factor in being able to go to the tourist sites conveniently, 4)channel of contact factor in being able to contact through agency, 5)process factor in having a convenient reservation process, 6) marketing promotion in having been advised in travel guidebook column, and 7) price factor in being suitable to their budgets.
Keywords: Promotion (chess); Hospitality; Customer Service Quality and Loyalty